Pengembangan Media Pembelajaran Papan Stik (Stick Board) pada Materi Operasi Hitung Perkalian - Akmal Hi. Dahlan; Fariami Kondihi (Peneliti.net, 2021)
This study aims to develop learning media for the stick board on the multiplication count operation material. This study uses a classroom action research approach. In this activity, researchers collaborated with mathematics subject teachers to carry out learning according to the plan that had been designed between the researcher and the subject teacher. The results of this study are presented in descriptive form, which describes the steps taken in each study. The results of the research on the use of stick board learning media on the multiplication count operation material in grade II SD Inpres Sakita students, showed that before using the learning media stick board, 12 students or 70.58% failed to qualify, 3 students or 17.64% who are less qualified, and two of them are sufficiently qualified and good (1 student or 5.88%). But after taking action by developing stick board learning, the results of student learning in cycle I were obtained, there were 1 student or 5.88% well qualified, 2 students or 11.76% sufficiently qualified, 4 students or 23.52% less qualified, and 10 students or 58.82% failed. Whereas in cycle II, 4 students or 23.52% were very well qualified, 8 students or 47.05% were well qualified, 3 students or 17.64% were sufficiently qualified, and the rest (2 students) 5.88% respectively -Each one is underqualified and failed.